The Influence of The Scientific Heritage of Ahmad AlFarghani on The Followers (Texas Journal of Multidisciplinary Studies, 2024)
In the article, the scientific work of the Uzbek encyclopedist Ahmed Al Fargani, known as Alfraganus in Europe, who played an important role in the scientific heritage not only of the Uzbek people, but also of the world, was an astronomer, mathematician, geographer and worked in other scientific fields. information about his legacy, the inexhaustible treasure he left to his descendants. And the influence of our scholar on his followers through his scientific heritage is widely covered.